Genetic diversity, population structure, and phylogenetic relationships of a widespread East Asia herb, Cryptotaenia japonica Hassk. (Apiaceae) based on genomic SNP data generated by dd-RAD sequencing - Wu, Baocheng; Wen, Jun; Lu, Ruisen; Zhou, Wei (Frontiers in Genetics, 2024)
Single-nucleotide polymorphisms (SNPs) represent the most prevalent form of genomic polymorphism and are extensively used in population genetics research. Using dd-RAD sequencing, a high-throughput sequencing method, we investigated the genome-level diversity, population structure, and phylogenetic relationships among three morphological forms of the widely distributed taxon Cryptotaenia japonica Hassk., which is native to East Asia. Our study aimed to assess the species status of C. japonica according to its genetic structure and genetic diversity patterns among 66 naturally distributed populations, comprising 26 C. japonica f. japonica, 36 C. japonica f. dissecta (Y. Yabe) Hara and 4 C. japonica f. pinnatisecta S. L. Liou accessions. Based on genomic SNP data generated by dd-RAD sequencing, we conducted genetic diversity, principal component, neighbor-joining (NJ) phylogenetic, admixture clustering, and population differentiation analyses. The findings revealed the following: (1) 539,946 unlinked, high-quality SNPs, with mean π, HO, HE and FIS values of 0.062, 0.066, 0.043 and -0.014, respectively, were generated; (2) population divergence was unaffected by isolation through distance; (3) six main distinct regions corresponding to geographic locations and exhibiting various levels of genetic diversity were identified; (4) pairwise FST analysis showed significant (P<0.05) population differentiation in 0-14% of populations among the six regions after sequential Bonferroni correction; and (5) three migration events (historical gene flow) indicated east-west directionality. Moreover, contemporary gene flow analysis using Jost's D, Nei's GST, and Nm values highlighted the middle latitude area of East Asia as a significant contributor to genetic structuring in C. japonica. Overall, our study elucidates the relatively low genetic differentiation and population structure of C. japonica across East Asia, further enhancing our understanding of plant lineage diversification in the Sino-Japanese Floristic Region.